The social value of carbon sequestered in Great Britain's woodlands - Julii Brainard; Ian J. Bateman; Andrew A. Lovett (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2005)
One tactic for mitigating climate change associated with human-origin CO2 releases is to promote C storage in biomass, particularly trees. The economic value of C storage associated with woodland can be compared to the costs (or benefits) of other strategies for mitigating climate change. Models were developed to calculate the rates of marginal carbon storage (or release) associated with live trees, forest floor litter, soils, wood products, harvest, fossil fuel used in manufacturing and C displacement from bio-fuels and products for representative British plantation species: Sitka spruce (Picea Sitchensis) and beech (Fagus sylvatica). Map databases of public and privately-owned woodlands were compiled for Great Britain. Marginal carbon gains (or losses) were determined for each woodland in the datasets. C flux was monetised using candidate parameters for the social discount rate (1, 3, 3.5 or 5%) and social value of carbon (US109.5, 1, 10 or 17.10/metric tonne). A conventional discount function was applied. Final results were expressed as Net Present Values, base year 2001. The modelling suggests that the minimum NPV (assuming discount rate=3% and social value of carbon = 1) of carbon sequestering in GB woodlands existing in 2001 was 82 million, with a expected further 72 million that might be added by subsequent afforestation. These figures rise dramatically if a discount rate of 1% and social value of sequestered carbon = 109.5/tonne are assumed. The total value of C stored in British woodland depends very much on the assumptions about appropriate discount rate and social value of sequestered carbon.
Keywords: 330; Carbon sequestration; Forestry Commission; green-house gases; peat; woodlands